(untitled) (British Journal of Global Ecology and Sustainable Development, 2023)
The article discusses the financing and advantages of cluster approaches in the agro-industrial complex in the grape industry. The foreign experience of creating and developing clusters is analyzed. The forecast and planning of cultivation of competitive industrial grape varieties is made. The issues of cultivation and the application of optimization methods in improving the structure of grape plantations, the production of grapes and its processing into finished products are considered.